A new critical variable analysis in processor-based systems - Bergaoui, S.; Vanhauwaert, P.; Leveugle, R. (2009 European Conference on Radiation and Its Effects on Components and Systems, 2009)
Determining the dependability of integrated systems with respect to soft errors is necessary for a growing number of applications. The most critical information must be identified when selective hardening is necessary to achieve good efficiency/cost trade-offs. In processor-based systems, the most critical variables must thus be identified in the application program. An improved algorithm for critical variable identification is described and validated with respect to fault injection results.